FACTORS INFLUENCING CUSTOMERS IN USING ISLAMIC BANKING SERVICE - Elanna Heidi Christanti; Dwi Wulandari; Bagus Shandy Narmaditya; Sugeng Hadi Utomo (UPT Penerbitan Universitas Jember)
This research is aimed to analyze factors influencing customers in using Islamic banking services. This research used mixed method. The quantitative method used to test the quality service, advantage, and availability of ATM. While the qualitative method used to test religion. The independent variables in this research are quality service, advantage, availability of ATM, and religion, meanwhile dependent variable is Islamic banking service. The data are taken directly from sixty respondents used purposive sampling technique, and using in-depth interview of BRI Syariah and BNI Syariah customers in Klojen, Malang. The quantitative data are processed and analyzed by multiple regression, while qualitative data analyzed by using triangulation technique. The result showed that service quality and advantage influence the using of Islamic banking service. The availability of ATM and religious do not influence the using of Islamic banking service.